1990
DOI: 10.1128/jvi.64.6.2653-2659.1990
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus-like, nonreplicating, gag-env particles assemble in a recombinant vaccinia virus expression system

Abstract: We report the assembly of human immunodeficiency virus (HIV)-like particles in African green monkey kidney cells coinfected with two recombinant vaccinia viruses, one carrying the HIV-1 gag and protease genes and the other the env gene. Biochemical analysis of particles sedimented from culture supernatants of doubly infected cells revealed that they were composed of gag proteins, primarily p24, as well as the env proteins gpl20 and gp4l. Thin-section immunoelectron microscopy showed that these particles were 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…RVF VLPs were generated by transient transfection of HEK-293 or 293-gag cells (HEK-293 cells that constitutively express Moloney murine leukemia virus (MoMLV) gag protein) with expression plasmids encoding the RVFV glycoproteins and the nucleoprotein (N). We initially focused upon the generation of chimeric (MoMLV gag-containing VLPs, designated RVF chimVLPs) because it has been previously shown that the inclusion of retroviral gag can increase the uniformity and quantity (Gheysen et al, 1989;Haffar et al, 1990;Haynes et al, 1991;Rovinski et al, 1992;Szecsi et al, 2006) and stability (Hammonds et al, 2003) of VLPs. In addition, MoMLV gag protein could have an adjuvant-like effect.…”
Section: Generation and Characterization Of Rvf Vlpsmentioning
confidence: 99%
“…RVF VLPs were generated by transient transfection of HEK-293 or 293-gag cells (HEK-293 cells that constitutively express Moloney murine leukemia virus (MoMLV) gag protein) with expression plasmids encoding the RVFV glycoproteins and the nucleoprotein (N). We initially focused upon the generation of chimeric (MoMLV gag-containing VLPs, designated RVF chimVLPs) because it has been previously shown that the inclusion of retroviral gag can increase the uniformity and quantity (Gheysen et al, 1989;Haffar et al, 1990;Haynes et al, 1991;Rovinski et al, 1992;Szecsi et al, 2006) and stability (Hammonds et al, 2003) of VLPs. In addition, MoMLV gag protein could have an adjuvant-like effect.…”
Section: Generation and Characterization Of Rvf Vlpsmentioning
confidence: 99%
“…Unlike most other enveloped RNA viruses, in which the viral glycoproteins appear to catalyze virus particle formation, assembly and release of retrovirus particles occur when capsid proteins are produced in the absence of the other gene products. Studies have shown that expression of the gag gene alone in a number of systems results in the efficient assembly and release of membrane-enveloped virions (2,3,10,12,18,28,29,35). Thus, the product of this gene has the structural information necessary to mediate intracellular transport, direct assembly of the capsid shell, and catalyze the process of membrane extrusion known as budding.…”
mentioning
confidence: 99%
“…Human immunodeficiency virus type 1 (HIV-1) assembly at the plasma membrane of infected cells is similar to the morphogenesis of type C retroviruses. The Gag precursor polyprotein of HIV-1 appears to be sufficient for virus assembly, since viruslike particles are formed in the absence of all other viral proteins (5,9,12,29,30). The Gag precursor of HIV-1 is first synthesized as a 55-kDa polyprotein (p55) and is subsequently cleaved by the viral protease to yield four mature Gag proteins: the matrix (MA) protein (p17); the capsid (CA) protein (p24); the nucleocapsid (NC) protein (p9); a proline-rich protein (p6); and two small peptides, p2 and pl (11).…”
mentioning
confidence: 99%